1994
DOI: 10.2136/sssaj1994.03615995005800030008x
|View full text |Cite
|
Sign up to set email alerts
|

Unsaturated Hydraulic Conductivity from Transient Multistep Outflow and Soil Water Pressure Data

Abstract: Soil water retention and unsaturated hydraulic conductivity functions [K(6)] estimated by the inverse solution technique through minimization of differences between measured and simulated transient outflow may be nonunique and differ from independently measured soil hydraulic data. Numerical and experimental studies have shown the benefit of using simultaneously measured soil water pressure head in the estimation of the soil water retention curve by the inverse technique. In this experimental study, soil water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
119
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(122 citation statements)
references
References 0 publications
3
119
0
Order By: Relevance
“…Eching et al (1994) in their study used, in addition to the cumulative drainage data, also water contents as input for the inversion in order to optimize the soil water retention and hydraulic conductivity curves. The initial condition was given by measured initial water contents of both the stemflow and throughfall areas.…”
Section: Inverse Solution Approachmentioning
confidence: 99%
“…Eching et al (1994) in their study used, in addition to the cumulative drainage data, also water contents as input for the inversion in order to optimize the soil water retention and hydraulic conductivity curves. The initial condition was given by measured initial water contents of both the stemflow and throughfall areas.…”
Section: Inverse Solution Approachmentioning
confidence: 99%
“…Faster and more flexible alternatives have been sought, the most popular of which is inverse modeling of transient flow data to determine the P c (S w ) and k rw (S w ) functions simultaneously by optimization (i.e., least squares estimation of the parameters in Brooks-Corey, van Genugthen-Mualem or other empirical models of the hydraulic functions) [Kool et al, 1987]. This approach has been applied to data obtained from onestep [e.g., van Dam et al, 1992] and multistep outflow [e.g., Eching et al, 1994;Nützmann et al, 1998], evaporation [e.g., Romano and Santini, 1999] and centrifuge experiments [Šimůnek and Nimmo, 2005]. Posed as an inverse problem, however, determination of soil hydraulic functions is complicated by issues of parameter nonuniqueness and identifiability.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, the multistep method was suggested, where the pressure at the boundary is changed in several small steps (van Dam et al, 1990). Eching et al (1994), van Dam et al (1994), Crescimanno andIovino (1995), andZurmühl (1996) demonstrated for the van Genuchten/Mualem model that the multistep method is superior to the one-step method because the hydraulic parameters are less correlated.…”
Section: Transient Laboratory Methodsmentioning
confidence: 99%